Surface evolution of vermicular cast iron in ultra-high temperature combustion with different single-pulsing duration. (November 2022) - Tang, Chengwei; Liu, Lei; Yang, Zhong; Tao, Dong; Li, Jianping; Guo, Qiaoqin; Zhen, Jieru; He, Yilei; He, Hongxiao
Highlights: The thermal impact test of vermicular cast iron was carried out by using high temperature combustion with different single loading durations. With increasing of single pulsing duration, the mass, thickness and roughness were increased. Oxidation was the main reason for the above changes. Phase transition occurred during thermal impact, resulting in the increase of hardness. Abstract: The key components in combustion chamber of high power density diesel engines are apt to be damaged rapidly under abnormal combustion. To investigate the surface damage behavior and evolution mechanism of vermicular graphite cast iron in unsteady combustion, a self-developed plasma thermal shock test method was adopted. And the effect of the single-pulsing duration (0.2, 0.5, 5, and 50 s) of combustion on reciprocating thermal shock characteristics was mainly studied. Results showed that as the sample with the longest loading duration (50 s) exhibited the highest mass gain rate (0.05 mg/s), thickness growth rate (0.096 μm/s), roughness (1.889 μm), and hardness (515 HV). The cumulative thickening and spalling of the oxide layer during the plasma impact is the main cause of the changes in ablation rate and surface roughness. And the bainite phase transformation in the heat affected zone increased the hardness of the material.